Pengaruh Dimensi Kualitas Pelayanan Terhadap Minat Servis Pada Bengkel AHASS Setia Kawan Kandangan Kediri - Rani Suzika; Tri Sudarwanto; Rohmad Prio Santoso (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2021)
This purpose of this study was determine the effect of variables from the dimensions of service quality on interest in service at AHASS Setia Kawan Kandangan Kediri Workshop. The method used in this research is quantitative method. Population 600. The sample size is90 respondents. The analysis method is multiple linear regression. Hypothesis testing through statistical tests, namely t test (partial) and F test (simultaneous). The results conclude that the physical evidence variable tangibles affected the interset in servicing the AHASS Setia Kawan Kandangan Kedir Workshop of 2.286 with a significant 0.025. The Reliability variable has a partially effect on service interest in the loyal AHASS Workshop Kawan Kandangan Kediri of 2.600 with a significant 0.011. Responsiveness variable partially influenced the service interest in the AHASS Setia workhsop Kawan Kandangan Kediri of 2,388 with a significant 0.019. Assurance variable partially influences service interest in AHASS Setia Kawan Kandangan Kediri workshop of 2.352 with significant 0.021. Emphaty variable has partial effect on service interest in AHASS Setia Kawan Kandangan Kediri Workshop of 3.598 with a significant 0.001. The variables of phsysical evidence tangibles, realibility, responsives, assuarance, emphaty variables influence simultaneously ti service interest in the workshop of AHASS Setia Kawan Kandangan Kediri of 16,271 with a significant 0.000. Keywords: Tangible; Realibility; Responsiveness; Assurance; Emphaty; Service Interest